An Antenna-Theory Method for Modeling High-Frequency RF Coils: A Segmented Birdcage Example - Xin Chen; Victor Taracila; Timothy Eagan; Hiroyuki Fujita; Xingxian Shou; Tanvir Baig; Robert Brown (International Journal of Antennas and Propagation)
We suggest that center-fed dipole antenna analytics can be employed in the optimized design of high-frequency MRI RF coil applications. The method is illustrated in the design of a single-segmented birdcage model and a short multisegmented birdcage model. As a byproduct, it is shown that for a long single-segmented birdcage model, the RF field within it is essentially a TEM mode and has excellent planar uniformity. For a short shielded multisegmented birdcage model, the RF field is optimized with a target-field approach with an average SAR functional. The planar homogeneity of the optimized RF field is significantly improved compared with that of a single-segmented birdcage model with the same geometry. The accuracy of the antenna formulae is also verified with numerical simulations performed via commercial software. The model discussed herein provides evidence for the effectiveness of antenna methods in future RF coil analysis.